The Three Rhotic Phonemes in Ṭyare Neo-Aramaic - Mutsafi, Ḥezi (Aramaic studies, 2014)
Whereas many North-Eastern Neo-Aramaic (nena) dialects exhibit two rhotic (R-) phonemes, mostly an alveolar /r/ as opposed to an emphatic alveolar /ṛ/, a striking feature related to rhotic differentiation, hitherto attested only in the Christian nena dialect of Bariṭle, is a threefold distinction of retroflex, alveolar and emphatic alveolar R-phonemes. This article demonstrates that such a distinction exists also in the Christian nena dialect-cluster of Ṭyare, discusses the nature and distribution of each of the three R-phonemes in Ṭyare, and suggests a diachronic account of the threefold split of r in this dialect-cluster.